DESAIN ALTERNATIF ALAT PENJEMUR PAKAIAN YANG ADA DI PASARAN - Kumalasari, Ika Nuning; Muladi, Edy (Anggada : Jurnal Desain dan Seni, 2020)
Clothesline tools are used as the right means of placing small and large amounts of laundry clothes. In terms of design developments, it can be said that clothesline has developed and innovated quite fast since the early 2000s. However, in a densely populated city like Jakarta, not all laundry equipment functions as it should. From the research conducted by the author, some respondents who live in several areas in Jakarta such as in the densely populated house, the majority of respondents said that they do not have a large drying space or area and this drying area is not exclusively used for drying clothes but is a versatile and multifunctional area. Such as parking vehicles and storing other household objects. Therefore the span dimension factor when it is in use or how to move the equipment when it is not in use is the main concern. Then Jakarta has a fairly high average temperature, which is in the range of 25-33 degrees Celsius so that not all materials can be used for clotheslines, the materials used must have resistance to weather which has high temperatures. From some of the existing problems, the writer wants to develop several alternative designs of clothes drying tools on the market by updating the system, structure, or aesthetics so that they can function properly.